Vampires : myths and metaphors of enduring evil - Day, Peter (Amsterdam ; New York, NY : Rodopi, 2006)
In the modern world vampires come in all forms: they can be perpetrators or victims, metaphors or monsters, scapegoats for sinfulness or mirrors of our own evil. What becomes obvious from the scope of the fifteen essays in this collection is that vampires have infiltrated just about every area of popular culture and consciousness. In fact, the way that vampires are depicted in all types of media is often a telling signifier of the fears and expectations of a culture or community and the way that it perceives itself; and others. The volume's essays offer a fascinating insight into both vampires.
Introduction; PART I Legend of the Vampire; Getting to know the Un-dead: Bram Stoker, Vampires and Dracula; "One for Ever": Desire, Subjectivity and the Threat of the Abject in Sheridan Le Fanu's Carmilla; Sex, Death, and Ecstasy: The Art of Transgression; The Name of the Vampire: Some Reflections on Current Linguistic Theories on the Etymology of the Word Vampire; The Discourse of the Vampire in First World War Writing; "Dead Man Walking": The Historical Context of Vampire Beliefs; Vampire Dogs and Marsupial Hyenas: Fear, Myth, and the Tasmanian Tiger's Extinction.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Vampires; Vampires; SOCIAL SCIENCE -- Folklore & Mythology; Vampires